Probing the effects of strong electromagnetic eields with charge-dependent directed flow in Pb-Pb collisions at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; Ohlson, Alice; et al. (Physical review letters, 2020)
The first measurement at the LHC of charge-dependent directed flow (v(1)) relative to the spectator plane is presented for Pb-Pb collisions at root s(NN) = 5.02 TeV. Results are reported for charged hadrons and D-0 mesons for the transverse momentum intervals p(T) > 0.2 GeV/c and 3 < p(T) < 6 GeV/c in the 5%-40% and 10%-40% centrality classes, respectively. The difference between the positively and negatively charged hadron v(1) has a positive slope as a function of pseudorapidity eta, d Delta v(1)/d eta = [1.68 +/- 0.49(stat) +/- 0.41(syst)] x 10(-4). The same measurement for D-0 and (D) over bar (0) mesons yields a positive value d Delta v(1)/d eta = [4.9 +/- 1.7(stat)] +/- 0.6(syst)] x 10(-1), which is about 3 orders of magnitude larger than the one of the charged hadrons. These measurements can provide new insights into the effects of the strong electromagnetic field and the initial tilt of matter created in noncentral heavy ion collisions on the dynamics of light (u, d, and s) and heavy (c) quarks. The large difference between the observed Delta v(1) of charged hadrons and D-0 mesons may reflect different sensitivity of the charm and light quarks to the early time dynamics of a heavy ion collision. These observations challenge some recent theoretical calculations, which predicted a negative and an order of magnitude smaller value of d Delta v(1)/d eta for both light flavor and charmed hadrons.
Gesehen am 23.10.2020
A Large Ion Collider Experiment Collaboration: S. Acharya, V. Angelov, M. Arslandok, M. Danisch, V. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D. Weiser, B. Windelband, A. Yüncü [und 977 weitere]